2016
DOI: 10.3109/0886022x.2016.1165070
|View full text |Cite
|
Sign up to set email alerts
|

Urinary markers of acute kidney injury in newborns with perinatal asphyxia*

Abstract: Background: Acute kidney injury (AKI) affects up to 60% of severely asphyxiated neonates. The diagnosis of AKI can be and is further challenged by a lack of good biomarkers. We studied the role of novel markers for AKI, neutrophil gelatinase-associated lipocalin (NGAL), interleukin-8 (IL-18), Netrin-1 (NTN-1), and sodium hydrogen exchanger isoform 3 (NHE3) on development and early diagnosis of AKI in newborns with perinatal asphyxia (PA). Methods: Forty-one newborns with a diagnosis of PA (15 with AKI and 26 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 30 publications
0
30
0
1
Order By: Relevance
“…In our study, NGAL levels were lower in the urine in the preoperative period and it increased significantly in the postoperative period. Oncel et al [19] reported elevated urinary NGAL levels in the first day among patients with perinatal asphyxia. In the study by Tanigasalam et al [20], of the 120 neonates exposed to perinatal asphyxia, 55 (46%) patients developed AKI.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, NGAL levels were lower in the urine in the preoperative period and it increased significantly in the postoperative period. Oncel et al [19] reported elevated urinary NGAL levels in the first day among patients with perinatal asphyxia. In the study by Tanigasalam et al [20], of the 120 neonates exposed to perinatal asphyxia, 55 (46%) patients developed AKI.…”
Section: Discussionmentioning
confidence: 99%
“…The reference ranges for urinary netrin-1 in healthy adults and children have not been published in the literature to date. The only data concerning the normal values of urine netrin-1 concentrations come from control groups from studies conducted in patients with renal dysfunctions [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…What is even more noteworthy is the fact that the urinary netrin-1 concentrations seem to be a marker of perinatal asphyxia [12]. Significantly, higher urinary concentrations of netrin-1 within 48 h after birth were found in neonates with acute renal injury than in the non-AKI group [13].…”
Section: Introductionmentioning
confidence: 99%
“…This study was performed on preterm infants below 32 weeks of gestation age. Oncel NY et al [24] studied 41 cases of newborn with a diagnosis of perinatal asphyxia and classified the cases into AKI and non-AKI groups. The AKI group included 15 newborns and Non-AKI group included 26 newborns.…”
Section: Discussionmentioning
confidence: 99%